TRANSLATION OF NAMES OF POLISH HIGHER SCHOOLS AND THE RULE OF DILIGENT PREPARATION OF TRANSLATIONS AND FAITHFULNESS OF A SWORN TRANSLATION - ŁOMZIK, Magdalena (Comparative Legilinguistics, 2019)
Statutory obligation of a sworn translator to exercise special diligence obliges him to perform a diligent and faithful translation, including the names of institutions. In the process of translating names of Polish colleges, a translator may use German equivalents, which have been made available in a publicly available German database ANABIN, which contains information that make it easier for offices and schools to decide in terms of recognizing educational qualifications. However, translation and thus, choice of wording is the responsibility of the translator exclusively. He must therefore approach the suggested equivalents critically; thereby, he may not automatically accept propositions without having verified them prior. The article undertakes to establish which of the proposed equivalents of names of Polish colleges violate the rule of diligent preparation of translations and faithfulness of a sworn translation as well as the consequences of incorrect translations of university names.